Dressel 24 similis amphorae of Roman Imperial period from Erythrai - Kırkanlı, Ebru (Rei Cretariae Romanae Fautorum Acta, 2024)
This study aims to present the locally produced Erythrai Dressel 24 Similis amphorae found during the excavations of the Erythrai 1977-1988 season. During the excavations, many amphora types were found dating from the 5th century BC to the 11th century AD. Dressel 24 Similis amphorae, also known as cup-shaped rims, is one of the most important finds from Erythrai, and is dated from the 1st century BC to the 3rd century AD. Erythrai Dressel 24 Similis amphora samples were evaluated for similarity with other production centers with their morphology and relative dating periods. Clay in two colors is an important feature of the group, it also shows similarity with Chian examples.